Calculations of the optical response of metallodielectric nanostructures of nonspherical particles by the layer-multiple-scattering method - N. Papanikolaou; G. Gantzounis; N. Stefanou (Proceedings of SPIE, 2008)
We present an efficient computational methodology for full electrodynamic calculations of metallodielectric nanostructures based on a multiple-scattering formulation of Maxwell's equations. The method, originally developed for systems of spherical particles (MULTEM code), is extended to systems of particles of arbitrary shape and applied to ordered structures of metallic nanodisks with an aspect ratio as large as five. We first discuss the particle plasmon resonances of single metallic nanocylinders of different aspect ratios. Then, we study the plasmonic excitations of square arrays of metal-dielectric-metal nanosandwiches and the optical response of a rectangular lattice of metallic nanodisks on a dielectric waveguide. Finally we analyse the photonic band structure of a simple cubic crystal of metallic nanodisks.